Evaluating the Efficiency of a Modified Solar Powered Pond Aerator System - P. Legamia, Benigno; D., Jr.; B. Singian, Adriano; D., Ed. (International Journal of Engineering and Technology, 2018)
In this contemporary world, fish may commonly die caused by warm water where the oxygen turns into a less soluble at an increased temperature or turns into a gas bubble from a carbon dioxide and ammonia which directly flow into the fish. One effective way to regulate fishkill is to guarantee the adequate amount of oxygen in the water. To lessen these pressing issues, if not to completely eradicate, a study to evaluate the efficiency of a developed Modified Solar Powered Pond Aerator System (SPPAS-500) had taken place. It is an apparatus that floats on the water which gives balanced oxygen level in the pond using the venturi air ejector technology. Furthermore, aside from direct utilization of the generated electrical power during daytime, the system also stores the surplus energy into the batteries for utilization during evening. The method used for evaluation is patterned with the data generated from application of the system in electrical and hydrological manner. Â Different instruments in measuring, testing and computing data are utilized to come up with significant, valid, reliable, authentic and accurate evaluation, analyses and conclusions. As a result, the SPPAS-500 is found to be capable of addressing the minimum aeration requirements needed by various size aquamarine enterprises.Â